2010
DOI: 10.4061/2010/514659
|View full text |Cite
|
Sign up to set email alerts
|

Salivary C-Reactive Protein in Hashimoto's Thyroiditis and Subacute Thyroiditis

Abstract: C-reactive protein (CRP), an acute-phase reactant, has been identified as a saliva-based biomarker of inflammation. The objective of the study was to estimate and compare salivary CRP levels in Hashimoto's thyroiditis (HT) and Subacute thyroiditis (SAT). The study included 30 HT patients who presented with clinical features of hypothyroidism, 15 SAT patients who presented with clinical features of hyperthyroidism, and 20 healthy age- and sex-matched euthyroid controls. CRP levels in saliva were estimated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Methods for saliva collection from primates have been used in free‐ranging settings (Higham et al, ), and similar or adapted methods are probably feasible for numerous (though clearly not all) primate species in free‐ranging populations. In saliva, many native analytes can be measured, including sympathetic axis correlates such as alpha‐amylase (e.g., rhesus macaques, Higham et al, ; bonobos, Beringer et al, ), haptoglobin (e.g., pigs, Gómez‐Laguna et al, ), and CRP (e.g., humans, Rao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Methods for saliva collection from primates have been used in free‐ranging settings (Higham et al, ), and similar or adapted methods are probably feasible for numerous (though clearly not all) primate species in free‐ranging populations. In saliva, many native analytes can be measured, including sympathetic axis correlates such as alpha‐amylase (e.g., rhesus macaques, Higham et al, ; bonobos, Beringer et al, ), haptoglobin (e.g., pigs, Gómez‐Laguna et al, ), and CRP (e.g., humans, Rao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by diff use lymphocytic infi ltration of the thyroid gland. Despite studies on autoimmune infl ammation, the pathogenesis of CAT still remains unclear (Rao et al 2010;Poplawska-Kita et al 2015).…”
mentioning
confidence: 99%
“…The study of salivary CRP levels in such two groups with thyrotoxicosis of different etiology may give new insight in this aspect, as indicated by other workers. [12] However we did not have an opportunity to study the same in our patients. A lot of information which is now available suggests that mild rise in serum CRP levels in CAT patients suggest ongoing low grade inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Salivary CRP also rises significantly in SAT and hence has been proposed as a helpful biomarker in differentiating such an inflammatory thyroid disorder from others. [12] Thus it has been observed that rise in CRP in blood or body secretion is most striking in SAT amongst all sorts of thyroid disorders. In various other fields of medicine, serum CRP has evolved as a sensitive marker for underlying inflammatory pathology, response to therapy and prognosis of the disease process.…”
Section: Introductionmentioning
confidence: 99%